2022
DOI: 10.3389/fcvm.2022.909204
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of cardiac magnetic resonance segmental myocardial strain for detecting microvascular obstruction and late gadolinium enhancement in patients presenting after a ST-elevation myocardial infarction

Abstract: BackgroundMicrovascular obstruction (MVO) and Late Gadolinium Enhancement (LGE) assessed in cardiac magnetic resonance (CMR) are associated with adverse outcome in patients with ST-elevation myocardial infarction (STEMI). Our aim was to analyze the diagnostic performance of segmental strain for the detection of MVO and LGE.MethodsPatients with anterior STEMI, who underwent additional CMR were enrolled in this sub-study of the CARE-AMI trial. Using CMR feature tracking (FT) segmental circumferential peak strain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…also studied patients in the acute phase after MI with an AUC of 0.91 for LV SCS and 0.74 for LV SLS for predicting infarct transmurality 75% 27 . Gräni et al studied patients approximately 3 days after STEMI with similarly high sensitivity for LV SCS to predict LGE (AUC = 0.84) as found in this cohort 17 . Yu et al .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…also studied patients in the acute phase after MI with an AUC of 0.91 for LV SCS and 0.74 for LV SLS for predicting infarct transmurality 75% 27 . Gräni et al studied patients approximately 3 days after STEMI with similarly high sensitivity for LV SCS to predict LGE (AUC = 0.84) as found in this cohort 17 . Yu et al .…”
Section: Discussionsupporting
confidence: 62%
“…Myocardial strain-imaging with FT, however, allows the calculation of regional deformation without the need for acquiring multiple additional sequences. Moreover, it has been proposed that FT CMR could have an incremental prognostic value to predict mortality after MI over LVEF and infarct size 16 and there is evidence that strain might be able to predict presence of MVO 17 . While global myocardial strain analysis is already implemented in various guidelines, segmental strain analysis is used restrictively due to lower reliability 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (26) developed a deep learning framework based on non-contrast cine CMR that could detect the presence, location, transmurality, and size of chronic myocardial infarction without relying on additional LGE images, demonstrating the diagnostic capabilities of routinely acquired non-contrast cine CMR images for chronic myocardial infarction diagnosis. Gräni et al (27) included 48 STEMI patients who underwent CMR after PCI. Their study showed that segmental strain in patients with STEMI had a good diagnostic performance in identifying MVO+ and excellent diagnostic performance for LGE+ segments.…”
Section: Discussionmentioning
confidence: 99%
“…CMR imaging was either performed on a 1.5 or 3.0 Tesla scanner (Magnetom Trio and Area, Siemens Healthineers, Erlangen, Germany) as described previously [ 4 , 7 , 9 ]. The application cvi41 (Circle Cardiovascular Imaging, Calgary, Canada) was used for postprocessing.…”
Section: Methodsmentioning
confidence: 99%
“…If required, values were either corrected for the peak strain at correct time to peak or excluded. Since reliability of segment based RLS is limited [ 9 ], segments were also summarized to different regions by calculating the mean RLS of summarized segments. Regions were defined as anterior (AHA-segments 1, 7, and 13), septal (segments 2, 3, 8, 9, 14), inferior (segments 4, 10, 15) and lateral (segments 5, 6, 11, 12, 16).…”
Section: Methodsmentioning
confidence: 99%